# Given : S(s) + O2(g) --> SO2 (g) Delta H= -296.1 kJ 2SO3(g) --> 2SO2(g) + O2(g) Delta H= 198.2 kJ How to find the Delta H for :2S(s)+3O2(g) --> 2SO3(g)?

Mar 15, 2018

We want $\Delta {H}^{\circ}$ for..

$2 S \left(s\right) + 3 {O}_{2} \left(g\right) \rightarrow 2 S {O}_{3} \left(g\right)$

#### Explanation:

We gots...

$\left(i\right)$ $S \left(s\right) + {O}_{2} \left(g\right) \rightarrow S {O}_{2} \left(g\right)$ ;DeltaH^@=-296.1*kJ*mol^-1

And...

$\left(i i\right)$ $2 S {O}_{3} \left(g\right) \rightarrow 2 S {O}_{2} \left(g\right) + {O}_{2} \left(g\right)$ ;DeltaH^@=+198.2*kJ*mol^-1

And we take $2 \times \left(i\right) - \left(i i\right)$...

$2 S \left(s\right) + 2 {O}_{2} \left(g\right) + \cancel{2 S {O}_{2} \left(g\right)} + {O}_{2} \left(g\right) \rightarrow 2 S {O}_{3} \left(g\right) + \cancel{2 S {O}_{2} \left(g\right)}$

.....the which gives...

$2 S \left(s\right) + 3 {O}_{2} \left(g\right) \rightarrow 2 S {O}_{3} \left(g\right)$

$\Delta {H}_{\text{rxn}}^{\circ} = \left(2 \times - 296.1 - 198.2\right) \cdot k J \cdot m o {l}^{-} 1 = - 790.4 \cdot k J \cdot m o {l}^{-} 1$